A Comparative Study of Laws in Indonesia and Malaysia Pertaining to the Crime of Domestic Violence - Chandra, Jessica (Jurnal Ilmu Hukum Kyadiren, 2025)
Domestic Violence (DV) is a significant issue in Indonesian society, with the majority of victims being women, particularly wives, who endure physical, psychological, sexual, or economic abuse perpetrated by their husbands. A deeply rooted patriarchal culture often discourages victims from reporting such violence, as it is regarded as a private matter. Moreover, social stigma leads victims to feel ashamed, largely due to cultural norms, religious beliefs, and limited legal awareness. This study employs a normative legal approach to compare domestic violence laws in Indonesia and Malaysia. The comparison examines the number of articles, types of offenses, classifications of injuries, and criminal penalties. In Indonesia, domestic violence is addressed under Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The findings highlight both similarities and differences in the two countries’ policies regarding domestic violence.